ASSESSMENT OF TOLERABILITY OF PNEUMOCOCCAL CONJUGATE VACCINE AND THE INFLUENCE OF THE VACCINATION ON THE INCIDENCE OF RESPIRATORY INFECTIONS IN CHILDREN DURING THE FIRST FIVE YEARS OF LIFE IN THE SAKHA REPUBLIC (YAKUTIA) - N.V. Savvina; V.B. Egorova (Union of pediatricians of Russia, 2011)
One of the most frequent etiology agent of upper respiratory tract infection is pneumococcus. Most susceptible to this infection are children under 5 years old. It is known that the only effective prevention of pneumococcal infections is a specific immunoprophylaxis. Authors represent their own experience of vaccination for the child population at risk. The analysis of the effectiveness of 7-valent conjugate pneumococcal vaccine in 596 children under 5 years old is demonstrated. The immunization is revealed low reactogeni city of vaccine and evident clinical effect. Thus, this vaccine may be recommended for inclusion in a regional immunization schedule in Republic of Sakha (Yakutia).Key words: children, pneumococcal infection, vaccine prophylaxis.